What determines firms' access to credit in the absence of effective economic institutions: Evidence from China - Tong Fu (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The existing literature suggests that economic institutions determine the allocation of resources for economic growth. As an important counterexample, although China has one of the world's fastest-growing economies, its legal and financial systems are underdeveloped. With evidence from China, the author confirms that government intervention positively and causally determines firms' access to credit. The author further provides evidence that government intervention enables firms' profit through facilitating access to credit. This evidence confirms that the mechanism of government intervention allows firms' access to credit and then enables the firms to obtain relatively large profits. Ultimately, this paper reveals that, in the absence of effective economic institutions, government intervention determines firms' access to credit.
Keywords: O17; G21; G28; C51; 330; access to credit; government intervention; mediation effect